The Governmentality of Self and Others: Cases of Homosexual Clergy in the Communist Poland - Laddach Agnieszka (Open Theology, 2025)
In this article, I analyze the biographical sources of two priests identified as homosexuals by the Polish Security Services. I examined the sexual agency and governmentality of the clergymen in relations with security officials, the Church people, and possible sexual partners together with the clergymen’s attitude to the moral teaching of the Church. Following Michel Foucault’s lectures, I show that the discourse about homosexuality, and eventual gay acts, seemed to be their Aufklärung (enlightenment) that brought out their agency. Consequently, one of the priests did not follow a Foucaldian call to become the liberator of others to think for themselves, whereas the second priest assumed such a role by suggestively encouraging believers to follow their spiritual struggles with God. My research demonstrates that sexual agency is subject to the negotiation of self-images with each other and external actors. In Communist Poland, the priests’ governmentality of self and others and their agency highlight the emotional dynamics of interactions with powerful institutions, i.e. the state and the institutional Church.